Concept of Paradigm Shift in Public Health Research - Khanal, K (Kathmandu University Medical Journal, 2014)
No abstract available. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10984 Kathmandu University Medical Journal Vol.10(4) 2012: 1-2